Implementasi Sarira Samskara dalam Upacara Manusa Yadnya di Bali dan Perannya dalam Transformasi Tubuh serta Jiwa - Harsananda, Hari; Wedana, I Wayan Bagus Citra (Sphatika: Jurnal Teologi, 2026)
This article aims to examine the concept of sarira samskara in ancient Hindu teachings and its implementation in the manusa yadnya ceremony in Bali, while analyzing its role in the process of transformation of the human body and soul. This study uses a qualitative approach with a library research method, through a review of relevant holy scriptures, palm-leaf manuscripts, books, and scientific journals. The results of the study indicate that sarira samskara is a series of purification ceremonies that accompany the journey of human life from the conception phase (garbhadana) to marriage (wiwaha). In the Balinese context, this concept is embodied in various forms of manusa yadnya such as magedong-gedongan, nyambutin, otonan, metatah, pawintenan, mejaya-jaya, and pawiwahan. Each stage of the ceremony functions not only as a symbolic ritual, but also as a medium of spiritual education that transforms the physical aspect through bodily purification, and the spiritual aspect through the instillation of dharmic values, mantras, prayers, and character building. Thus, sarira samskara (manusa yadnya) can be understood as a holistic development system that guides humans towards awareness of the essence of the self as atman, a divine spark that is in the process of moving towards the ultimate goal of life, namely moksa.